Penanaman Nilai Kewirausahaan Melalui Kegiatan Market Day di UPT SPF SD Inpres Perumas Makassar - Alwy*, Megawati; *, Elpisah; Rahman, Nawir; Nasruddin, Nurfitraeny (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims: 1) To find out what the Market Day education model is at SD Inpres Perumnas Makassar. 2) To find out the process of instilling entrepreneurial values in Market day education at SD Inpres Perumnas Makassar. 3) To determine the results of instilling entrepreneurial values in the formation of students' cognitive, affective and psychomotor aspects. This research uses descriptive qualitative research. This data collection technique uses an interview guide which was distributed to the sources for this research, namely school principals, teachers and students, as well as parents at UPT SPF SD Inpres Perumas Makassar. The research results obtained 1). The market day education model is based on the vision and mission of SD Inpres Perumnas Makassar, namely forming a spirit of independence and leadership in accordance with the potential intelligence and development of students. Market day learning is designed to foster entrepreneurial values in students which is done by integrating entrepreneurial concepts in all subjects through certain learning themes in class and selling practices inside and outside school. 2). The Market Day learning strategy in class is carried out by integrating entrepreneurship concepts in lessons. Instilling entrepreneurial values in practical selling activities in school and outside school. The obstacles to market day management are that it is not neatly organized, administration and program planning are not running well and parents are not intensive enough in market day activities. 3) Instilling entrepreneurial values through the market day education model is the formation of cognitive, affective and psychomotor aspects based on students' experiences and development criteria (i) in the market day curriculum.